Frequency of 25-Hydroxyvitamin D Deficiency in Pediatric Patients with Immune Thrombocytopenia: Disease Phase and Therapy Options - Abbas, Huda K.; Saleh, Basil O.; Ghali, Hassanain H. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Hypovitaminosis D can cause immunological irregularities in the development of immune thrombocytopenia. Objectives: To identify the frequency of low levels of 25-hydroxyvitamin D in children with Immune thrombocytopenia (ITP), and to assess the effect of the disease phase and type of treatment on vitamin D level. Methods: This case-control study was carried out on 88 children (63 had been diagnosed with immune thrombocytopenia and 25 healthy children as controls) during November 2023 and April 2024. The patients were sub-grouped according to global classification of vitamin D level into three groups: less than 10 ng/ml (n = 47), 10–20 ng/ml (n = 16), and 20-30 ng/ml (none of the patients or controls fell in this group). The cases were sub-classified according to their disease phase: Acute (n = 21), persistent (n = 24), and chronic (n = 18). The serum 25-hydroxyvitamin D level was measured using the enzyme-linked immunosorbent assay (ELISA) technique. Results: Around 75% of ITP children had a serum 25-hydroxyvitamin D level of less than 10 ng/ml. The mean (± SEM) values of the serum 25-hydroxyvitamin D of the ITP children of acute (9.5±1.84 ng/ml) and chronic (8.0±1.13 ng/ml) phases were lower than those of controls (10.0±1.32 ng/ml, p > 0.05), but not significantly so. The mean values of 25 hydroxyvitamin D of ITP children were lower than those of the controls, irrespective of the type of treatment. Conclusion: Vitamin D deficiency is prevalent among children with immune thrombocytopenia, particularly those in the chronic phase.